Patients’ satisfaction and quality of life after dental implant rehabilitation: A cross-sectional study - Saad, Noor Asyikin; Omar, Nuzul Izwan; Ahmad Yaziz , Yuhaniz; Abdul Manab, Enny Esdayanty (IIUM Journal of Orofacial and Health Sciences, 2023)
Perceiving patients’ satisfaction and improving patients’ quality of life is a challenging task. This study aimed to assess the patient’s quality of life and satisfaction after receiving a dental implant rehabilitation. All patients with dental implant placed between 2015 and 2019 were included. A self-administered questionnaire consisted of a demographic, patient satisfaction assessment, and the short version of the Malaysian Oral Health Impact Profile, S-OHIP (M) questionnaire. The patients indicated their rate on a 5-point Likert scale from 0 to 4. Statistical analyses were made using the SPSS version 26, statistical significance was considered for p<0.05. A total of 58 patients with 91 implants completed the questionnaire were included. In general, the majority of participants 56 (96.6%) were satisfied with the dental implant mainly with the speech function and maintenance procedure. The Cronbach’s Alpha coefficient for the nine items of satisfaction was 0.798. The mean OHIP-14 score was 2.1 (SD: 3.11; range from 0 to 12) with the highest score for psychological discomfort (mean: 0.92, SD: 1.35) and the lowest score for psychological disability (mean: 0.00, SD: 0.00). All domains of OHIP-14 had Coefficient of Variance, CV > 1 (ranged from 1.47 to 8.77) which considered being high variance. Overall, all participants had OHIP-14 scores ranging from 0 to 12 which can be considered a low score that indicated higher Oral Health-Related Quality of Life (OHRQoL). The correlation between patient satisfaction and quality of life is significant (P<0.05).